Eksplorasi Potensi Antioksidan dan Sitotoksisitas Metabolit Sekunder Ekstrak Kulit Buah Kakao (Theobroma cacao L) Pada Sel WiDr - Chusniasih, Dewi; Tutik, Tutik (Jurnal Analis Kesehatan, 2022)
Antioxidant compounds have the ability to inhibit or prevent oxidative damage to target molecules. Oxidative damage is one of the agents that play a role in the development of cancer cells. It is interesting to conduct research to find other anti-cancer compounds in order to minimize the side effects of these anti-cancer drugs.This study aimed to examine the antioxidant activity and cytotoxicity in vitro of acetone extract of cocoa pods (Theobroma cacao L.) on WiDr cells. This research is an experimental study, to see the effect of giving cocoa pod peel extract on the inhibition of free radicals, and WiDr cell death. Samples were extracted using 80% acetone. The antioxidant activity test was carried out using the DPPH method. The anti-cancer activity test was carried out using the MTT assay method. The test results obtained the IC50 value which indicates the cell death rate related to the concentration of the extract using linear regression analysis, as well as the percentage of antioxidant inhibition. Cocoa pod peel extract has an IC50 of 15.41 ppm and is classified as a very strong antioxidant. The IC50 value of the extract for vero cells was 528.13 ppm, while the IC50 value of the extract for WiDr cells was 47.47 ppm. This study showed that cocoa pod peel extract was classified as a very strong antioxidant component and was active in inhibiting the growth of WiDr cells and not actively inhibiting the growth of normal vero cells.Â